Detecting Disparities in Medication Management Among Limited English Proficient and English Proficient Home Health Patients. Issue 1 (February 2020) - Miner, Sarah M.; Squires, Allison P.; Ma, Chenjuan; McDonald, Margaret V.; Jones, Simon A.
According to the U.S. census Bureau, close to 20% of the U.S. population speaks a language other than English at home. Home health care (HHC) patients who speak English less than very well or have limited English proficiency (LEP) are at an increased risk for medication mismanagement and serious health consequences. The purpose of this study was to examine if there were differences in medication management between English-speaking patients and patients with LEP receiving HHC services. Data for this cross-sectional observation study were collected from 2010 to 2014. Medication management was measured by two items in the Centers for Medicare and Medicaid Services–mandated Outcomes Assessment Information Set (OASIS). All patients in the database who were taking medications and had a valid admission and discharge assessment from HHC were included in the analysis. Inverse probability of treatment weighting (IPTW) with a marginal structural model was used to address potential imbalances in observed patient characteristics when estimating the effect of having LEP or being an English-speaking HHC patient on changes in medication management over the course of a HHC episode. Estimates from marginal structural model with inverse probability weighting indicate that being LEP was associated with less improvement in medication management and increased likelihood of getting worse over the course of a HHC episode. This study is one of the first to demonstrate that patients with LEP experience disparities in medication management when compared to English-speaking patients in HHC.